GABAB receptor-mediated inhibition of spontaneous inhibitory synaptic currents in rat midbrain culture. - Rohrbacher, Jutta; Jarolimek, Wolfgang; Lewen, Andrea; Misgeld, Ulrich (The journal of physiology, 1997)
1. Tight-seal, whole-cell recording was used to study GABAB receptor-mediated inhibition of spontaneous inhibitory synaptic currents in cultured rat midbrain neurones. 2. Spontaneous miniature inhibitory postsynaptic currents (mIPSCs) were recorded in tetrodotoxin (TTX), Cd2+ and Ba2+. (R)-(-)-baclofen reduced the frequency of mIPSCs through a presynaptic mechanism. The EC50 for this effect was 7 microM. It was antagonized by the GABAB receptor antagonist CGP55845A (0.5 microM). 3. In pertussis toxin (PTX)-treated cultures, some GABAB receptor-mediated reduction of the frequency of mIPSCs persisted. In contrast, PTX treatment totally abolished inhibition of miniature excitatory postsynaptic currents (mEPSCs). 4. In PTX-treated cultures, a saturating concentration of (R)-(-)-baclofen inhibited action potential-generated IPSCs but no EPSCs. 5. PTX treatment abolished the (R)-(-)-baclofen-mediated inhibition of high voltage-activated somatic Ca2+ currents and of spontaneous IPSCs depending on presynaptic Ca2+ entry. 6. We conclude that cellular mechanisms underlying GABAB receptor-mediated inhibition of mIPSCs contribute to auto-inhibition of GABA release.